Korelasi Persepsi Kinestetik dan Rasa Percaya Diri Terhadap Hasil Tendangan Penalti Sepak Bola - Amir Supriadi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to determine the correlation between kinesthetic perception and self-confidence on the results of soccer penalty kicks by the players of the Medan State University Student Soccer Team. And to find out the joint correlation between kinesthetic perception and self-confidence on the results of the penalty kicks of the Medan State University Student Soccer Team players. The sample consisted of 30 players from the Medan State University Student Soccer Team who were selected by simple random sampling. The results of the research carried out are: in the first hypothesis there is a significant correlation between kinesthetic perception and the results of a soccer player's penalty kick at the State University of Medan obtained a t-count of 26.39 which is greater than the t-table of 1.70. The second hypothesis is that there is a significant correlation between self-confidence and achievement on the results of the soccer penalty kicks of the Medan State University team, which has a t-count of 6.59 and is greater than a t-table of 1.70. In the third hypothesis, there is a significant correlation between kinesthetic perception and self-confidence on the results of the Medan State University soccer penalty kick with a t-count of 160 which is greater than a t-table of 3.33. So it can be concluded that there is a significant relationship between variables and jointly on the penalty kick ability of the students of the Medan State University football team.